Private Activity in Infrastructure Down, But Still Around Peak Levels - Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
The report is about the private participation in infrastructure database. In 2008, 216 infrastructure projects with private participation reached financial or contractual closure in 48 low- and middle-income countries. These involve investment commitments (hereafter, investment) of US$66.5 billion. Infrastructure projects implemented in previous years had additional commitments of US$87.9 billion, bringing total investment in 2008 to US$154.4 billion. That represents a drop of 4 percent from the level reported in 2007. Investment in new projects accounted for the decline, falling by 12 percent from the level in 2007. By contrast, investment in projects implemented in previous years was up 3 percent from 2007. When investment is classified by type, it is payments to governments (such as concession or lease fees and divestiture revenues) that explain the drop in total investment. Such payments totaled US$19.1 billion, 42 percent lower than in 2007 and the lowest since 2004. By contrast, investments in physical assets grew by 6 percent from 2007 to reach US$135.3 billion, the highest level in 1990-2008.